2014
DOI: 10.1016/j.ijnurstu.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nurse prescribing: A systematic review

Abstract: The effects of nurse prescribing on medication and patient outcomes seem positive when compared to physician prescribing. However, conclusions must remain tentative due to methodological weaknesses in this body of research. More randomised controlled designs in the field of nurse prescribing are required for definitive conclusions about the effects of nurse prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 51 publications
(159 reference statements)
3
117
1
3
Order By: Relevance
“…The present results correspond with a study by Gielen et al [6]. A systematic review of 35 selected publications demonstrated that both objectively measured quality of care and patient satisfaction were higher (or at least comparable) in the case of nursing care rather than the one provided by physicians.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present results correspond with a study by Gielen et al [6]. A systematic review of 35 selected publications demonstrated that both objectively measured quality of care and patient satisfaction were higher (or at least comparable) in the case of nursing care rather than the one provided by physicians.…”
Section: Discussionsupporting
confidence: 91%
“…In the world literature (ProQuest, Google-scholar, PubMed, search dates: between April 1 st , 2001 and April 1 st , 2015, language: English, key words: nurse prescribing, nurse prescribers) there were a number of publications relating to the assessment of the fact that nurses were given the power to write prescriptions and refer patients for diagnostic tests [2,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review [38] reported that nurses prescribe for a wide range of patients in comparable ways to physicians. Patients were generally more or equally satisfied with the care provided by nurses compared to the traditional care provided by physicians.…”
Section: Pragmatic Process and Outcome Measuresmentioning
confidence: 99%
“…6 Além do Brasil, países como Austrália, Canadá, França, Reino Unido, EUA, Suécia, Botswana, Zâmbia, Nova Zelândia, Holanda, África do Sul e Irlanda já regulamentaram a prescrição de medicamentos pela enfermagem. [7][8] Estender o direito de prescrição para o enfermeiro possui diversas motivações, como a expectativa de contribuição na otimização e eficácia do cuidado ao usuário, melhoria da qualidade e continuidade do tratamento prescrito, bem como a possibilidade de um uso mais eficiente do tempo e dos recursos para os usuários. 8 A literatura aponta três modelos de prescrição de medicamentos por enfermeiro: prescrição independente, prescrição dependente e grupo protocolo.…”
Section: Introductionunclassified